A simple method to visualize results in nonlinear regression models - Daniel J. Henderson; Subal C. Kumbhakar; Christopher F. Parmeter (Institute for the Study of Labor (IZA), 2012)
A simple graphical approach to presenting results from nonlinear regression models is described. In the face of multiple covariates, 'partial mean' plots may be unattractive. The approach here is portable to a variety of settings and can be tailored to the specific application at hand. A simple four variable nonparametric regression example is provided to illustrate the technique.
Keywords: C1; C13; C14; 330; gradient estimation; dimensionality; kernel smoothing; nonlinear; mean plots; least squares cross validation